Basking sharks and oceanographic fronts: quantifying associations in the north‐east Atlantic. (7th March 2015) - Miller, Peter I.; Scales, Kylie L.; Ingram, Simon N.; Southall, Emily J.; Sims, David W.
Summary: Understanding the mechanisms that link oceanographic processes and marine vertebrate space use is critical to our knowledge of marine ecosystem functioning, and for effective management of populations of conservation concern. The basking shark Cetorhinus maximus has been observed in association with oceanographic fronts – physical interfaces at the transitions between water masses – exploiting foraging opportunities resulting from zooplankton aggregation. However, the scale, significance and variability of these associations have not previously been established. Here, we quantify the influence of thermal and chlorophyll‐ a fronts on basking shark habitat use in the north‐east Atlantic. We use animal‐mounted archival tracking together with composite front mapping via Earth Observation (EO) remote sensing to provide an oceanographic context to shark movements. We investigate levels of association with fronts occurring over two spatio‐temporal scales, (i) broad‐scale, seasonally persistent frontal zones and (ii) contemporaneous thermal and chl‐ a fronts. Using random walk simulations and logistic regression within an iterative generalized linear mixed modelling (GLMM) framework, we find that seasonal front frequency is a significant predictor of shark presence. Oceanographic metrics time‐matched to shark tracks indicate that sharks show a preference for productive regions and associate with contemporaneous thermal and chl‐ a fronts more frequently than could be expected at random. Moreover, we highlight the importance of front persistence and cross‐frontal temperature step, which appear to interact to affect the degree of prey aggregation along thermal fronts in this shelf‐sea system. Our findings confirm that surface frontal activity is a predictor of basking shark presence in the north‐east Atlantic, both over seasonal timescales and in near real‐time. These insights have clear implications for understanding the preferred habitats of basking sharks in the context of anthropogenic threat management and marine spatial planning in the region. Abstract : Lay Summary